2018
DOI: 10.1002/pssa.201700698
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Channel Layer Thickness on the Instability of Amorphous SiZnSnO Thin Film Transistors Under Negative Bias Temperature Stress

Abstract: In this study, amorphous silicon-zinc-tin-oxide thin film transistors (a-SZTO TFTs) are fabricated by radio-frequency magnetron sputtering at room temperature, and the influence of various channel thicknesses on their electrical performance and stability is report. Under the negative bias temperature stress, the transfer curve exhibits threshold voltage shift in the negative direction and degradation of subthreshold swing. In addition, the hump effect occurs in the thick channel, which is primarily due to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…The temperature dependency of TS was measured from room temperature to 353 K in intervals of 20 K. As O p increased, the amount of shift of V th (Δ V th ) decreased from 2.16 to 0.55 V. Regardless of the increase in O p , it was confirmed that V th moves toward the negative direction as temperature increases in the TS. It is expected that the thermal energy releases electrons in the trapped state inside the thin film with an increase in temperature 29 . We only applied the temperature parameter to analyze the effect on trap states inside the energy bandgap and did not add any additional stress, such as bias and illumination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature dependency of TS was measured from room temperature to 353 K in intervals of 20 K. As O p increased, the amount of shift of V th (Δ V th ) decreased from 2.16 to 0.55 V. Regardless of the increase in O p , it was confirmed that V th moves toward the negative direction as temperature increases in the TS. It is expected that the thermal energy releases electrons in the trapped state inside the thin film with an increase in temperature 29 . We only applied the temperature parameter to analyze the effect on trap states inside the energy bandgap and did not add any additional stress, such as bias and illumination.…”
Section: Resultsmentioning
confidence: 99%
“…3(d–f), including the obtained E a falling rate through the slope. The thermally activated drain current in the subthreshold region is obtained using the equation 29 where I D0 is the pre-factor, k is Boltzmann’s constant, T is the absolute temperature, and E a is the activation energy. The calculated E a falling rate increased systematically from 0.077 eV/V to 0.082 eV/V as O p increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ni content increased from 0 to 7.5 at%, the area proportion of O H decreased from 48.7% to 34.5%, indicating that oxygen vacancies were suppressed by Ni doping. The decrease in oxygen vacancies would result in reduced carrier concentration because oxygen vacancies serve as donors in AOSs . Figure shows EDS elemental maps encompassing In, Zn, Ni, and O obtained from the a‐IZNO thin films.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in oxygen vacancies would result in reduced carrier concentration because oxygen vacancies serve as donors in AOSs. [23] Figure 7 shows EDS elemental maps encompassing In, Zn, Ni, and O obtained www.advancedsciencenews.com www.pss-a.com www.advancedsciencenews.com www.pss-a.com from the a-IZNO thin films. In this study, an a-IZNO thin film with a Ni content of 6.6 at% was selected as a representative sample.…”
Section: Resultsmentioning
confidence: 99%